Cognitive–behavioral factors in tinnitus-related insomnia - Barry, Gemma; Marks, Elizabeth (Frontiers in Psychology, 2023)
Background: A significant proportion of individuals with distressing tinnitus also report insomnia. Limited but emerging evidence suggests tinnitus-related insomnia cannot be explained purely by the presence of tinnitus, and that sleep-related cognitive behavioural processes may play a key role in exacerbating tinnitus-related insomnia. Objectives: This study aimed to assess whether sleep-related cognitions and behaviours believed to maintain insomnia disorder are present for individuals with tinnitus-related insomnia. Methods: This between-groups study recruited 180 participants online for four groups: tinnitus-related insomnia (N=49), insomnia disorder without tinnitus (N=34), tinnitus sufferers who are good sleepers (N=38) and controls (N=59). They completed questionnaires assessing insomnia severity, sleep-related cognitions and behaviours, sleep quality, anxiety and depression. People with tinnitus completed a measure of tinnitus severity and rated the loudness of their tinnitus on a subjective measure. Results: Linear regression found that group was a significant predictor of sleep-related thoughts, behaviours and quality. Pairwise-comparisons showed the tinnitus-related insomnia group had significantly greater insomnia-related thoughts and behaviours and significantly worse sleep quality than tinnitus good sleepers. No differences were seen between tinnitus-related insomnia and insomnia groups. The tinnitus-related insomnia group had significantly higher depression, anxiety and tinnitus distress than tinnitus good sleepers. Conclusion: Findings suggest that tinnitus-related insomnia may be maintained by cognitive behavioural processes similar to those found in insomnia disorder, and such processes are more important than tinnitus severity when understanding sleep disturbance. People with tinnitus-related insomnia may benefit from treatments such as Cognitive Behavioural Therapy for insomnia.